(untitled) (Islas, 2025)
Introduction: Aware of its many distinctions from the rest of the region, the city of Cuenca (Ecuador) may be engaged in constructing a social imaginary rooted in sublimated self-perception, to which local speech would actively contribute. Based on this premise, the objective of the study was to describe specific forms of expression that, from an interpretive-social perspective, may reflect this collective construct. Methods: The study employed an anthropological sample characterized by theoretical and conceptual homogeneity, selected through purposive and convenience sampling. The data were analyzed from an interpretive-social perspective, in conjunction with an autoethnographic approach to the idiosyncrasy of Cuenca. Results: The analysis identified four pro-image and four proactive expressive forms, which appear to sustain the unreality of a social construct through the strategic use of language, fulfilling a dual illusionistic and propitiatory function. Conclusions: The expressions identified and described would constitute a speech tradition—potentially transmitted intergenerationally, though yet to be studied—embedded in processes of illusionism, simulation, and ostentation. These processes would uphold a firmly established Cuencan culture centered on image.